2016
DOI: 10.1172/jci83885
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte mitochondrial DNA drives nonalcoholic steatohepatitis by activation of TLR9

Abstract: Nonalcoholic steatohepatitis (NASH) is the most common liver disease in industrialized countries. NASH is a progressive disease that can lead to cirrhosis, cancer, and death, and there are currently no approved therapies. The development of NASH in animal models requires intact TLR9, but how the TLR9 pathway is activated in NASH is not clear. Our objectives in this study were to identify NASH-associated ligands for TLR9, establish the cellular requirement for TLR9, and evaluate the role of obesity-induced chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
328
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 394 publications
(359 citation statements)
references
References 17 publications
16
328
2
2
Order By: Relevance
“…As illustrated in Figure 1, A and B, the serum levels of particles were higher in EAU + RD patients compared with those in controls and EAU -RD. A previous study reported the presence of plasma mtDNA within MPs in mice and patients with nonalcoholic steatohepatitis (18). We therefore purified exosomes and MPs from human sera and examined whether mtDNA is located either in the MPs or exosomes in these subjects.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…As illustrated in Figure 1, A and B, the serum levels of particles were higher in EAU + RD patients compared with those in controls and EAU -RD. A previous study reported the presence of plasma mtDNA within MPs in mice and patients with nonalcoholic steatohepatitis (18). We therefore purified exosomes and MPs from human sera and examined whether mtDNA is located either in the MPs or exosomes in these subjects.…”
Section: Resultsmentioning
confidence: 98%
“…Circulating mtDNA levels were elevated and contributed to the pathogenesis of NASH by activating macrophages (18). It is possible that the elevation of mtDNA-enriched MPs in our E10d + 1B model also promotes macrophage activation and likely hepatic inflammation.…”
Section: Shown Scale Bar: 100 μM Arrows Indicate Mpo+ Cells (D-h) Wmentioning
confidence: 85%
See 3 more Smart Citations